Efficacy and safety of Bio 3D conduits composed of human umbilical cord–derived mesenchymal stromal cells: A proof-of-concept study in a canine ulnar nerve defect model - Fujita, Kazuaki; Ikeguchi, Ryosuke; Aoyama, Tomoki; Noguchi, Takashi; Yoshimoto, Koichi; Sakamoto, Daichi; Iwai, Terunobu; Miyamoto, Tetsuya; Miyazaki, Yudai; Akieda, Shizuka; Nagamura-Inoue, Tokiko; Nagamura, Fumitaka; et al. (Cell transplantation, 2025)
Peripheral nerve injuries involving nerve defects remain challenging to treat. Although autologous nerve grafting is considered the gold standard, it has notable limitations, including donor site morbidity. To address this, we developed a scaffold-free Bio 3D conduit composed of human umbilical cord–derived mesenchymal stromal cells (UC-MSCs) using bioprinting technology. In this study, we evaluated its efficacy and safety in a canine ulnar nerve defect model. At 10 weeks postoperatively, the Bio 3D group showed better motor and sensory recovery compared with the allograft group, as demonstrated by the pinprick test, electrophysiological studies, and hypothenar muscle wet weight (0.978 ± 0.100 vs. 0.637 ± 0.151, n = 3). Morphometric analysis revealed greater axonal regeneration, including larger myelinated axon diameters (4.27 ± 0.342 µm vs. 3.69 ± 0.161 µm, n = 3) and thicker myelin sheaths (0.621 ± 0.088 µm vs. 0.497 ± 0.021 µm, n = 3). Immunostaining showed that the number of transplanted UC-MSCs diminished over time, likely after exerting their therapeutic effects. No adverse events, systemic abnormalities, or distant human cell migration was observed. These findings suggest that UC-MSC–derived Bio 3D conduits are a promising alternative for peripheral nerve regeneration, especially for patients wishing to avoid donor nerve harvesting.